# How do you find the inverse of #y=e^x/(1+6e^x)#?

To find the inverse of ( y = \frac{e^x}{1 + 6e^x} ), follow these steps:

- Swap the roles of ( x ) and ( y ): ( x = \frac{e^y}{1 + 6e^y} ).
- Solve for ( y ).

[ x = \frac{e^y}{1 + 6e^y} ] [ x(1 + 6e^y) = e^y ] [ x + 6xe^y = e^y ] [ 6xe^y - e^y = -x ] [ e^y(6x - 1) = -x ] [ e^y = \frac{-x}{6x - 1} ] [ y = \ln\left(\frac{-x}{6x - 1}\right) ]

This is the expression for the inverse function ( f^{-1}(x) ) of the given function ( f(x) = \frac{e^x}{1 + 6e^x} ).

By signing up, you agree to our Terms of Service and Privacy Policy

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you find the inverse of #y=4^x# and is it a function?
- How do you identify the vertical asymptotes of #f(x) =2/(x^2+3x-10)#?
- How does the boundedness of a function relate to its graph?
- How do you find the inverse of # f(x)=e^(2x-1)#?
- Let # f(x)= -4x+3# and #g(x)= 1/(x+2)#, how do you evaluate f(g(x)) and g(f(x)) for x?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7